Project Report on Intelligent Traffic Management System Using Lab View - REJIN M A and SOUMITH S (2012)
INTERNAL GUIDE: D KAVITHA , ECE DEPT MVJCE
Keywords: Intelligent Traffic Management System Using Lab View